Differences in neonatal gastric tubes during insertion into a 3D model in relation to risk of potential perforation - Bartos, Hilda-Brigitta; Diez, Sonja; König, Alexander; Görlach, Jannis; Besendörfer, Manuel; Mahnken, Andreas H.; Drommelschmidt, Karla; Weiß, Christel; Müller, Hanna (Journal of pediatric gastroenterology and nutrition, 2024)
Objectives Perforation of esophagus or stomach is a potential complication during and after insertion of a gastric tube in neonates. The aim of this study was to analyze different types of gastric tubes in a three-dimensional (3D) model of neonatal esophagus and stomach regarding potential perforations. Methods A 3D model of esophagus and stomach was created based on computed tomography data of a term neonate. Three types of gastric tubes were inserted into the 3D model, the localization was examined by radioscopy and the behavior, stiffness and manageability of each gastric tube was evaluated. Results Insertion of gastric tubes with higher stiffness was easier. The rates of correct localization differed significantly between the gastric tubes with the highest rate of correct localization in the softest tube (48.5%) and the lowest rate in the tube with the highest stiffness (21.2%). Additionally, the softest tube showed the lowest rate of localization of its tip at the stomach wall. Conclusions The study illustrates differences between various types of gastric tubes regarding stiffness, behavior and resiliency. Softer gastric tubes may be beneficial. These differences may be relevant in neonatal care of very immature and very sick infants.
Zuerst veröffentlicht: 02. Februar 2024
Gesehen am 17.06.2024